Identifikasi kesalahan pembuktian matematis siswa pada materi aplikasi trigonometri - Herizal (Karoteh Utama, 2025)
Mathematical proof ability is a critical skill that fosters higher-order thinking in students. Due to the importance of this skill, a qualitative study was conducted to identify students' errors in solving mathematical proof problems related to trigonometric applications. The study involved 30 tenth-grade high school students from a school in Bandung, who were given four validated mathematical proof problems. In addition to written tests, several students were interviewed to further investigate the types of errors and their underlying causes. The findings revealed several categories of student errors: (1) incorrect application of the sine rule, cosine rule, and triangle area formulas; (2) failure to construct conjectures based on given patterns; (3) attempting to prove statements using examples; and (4) errors in algebraic manipulation processes. These errors were largely attributed to a lack of conceptual understanding and limited experience with mathematical proof. Therefore, the study recommends the development of instructional designs that emphasize mathematical proof activities to support students’ conceptual understanding and enhance their deductive reasoning skills.